AUTONOMY AND CONTROL IN EFL PROGRAMME MANAGEMENT - Ewen Arnorld (Indonesian JELT, 2006)
This article argues that issues of autonomy and control – who has autonomy and who has control over which decisions – are endemic in programme design, implementation and evaluation, and seriously impact programme success.  This argument is illustrated using data from an evaluation of an EFL Mentoring Programme designed to train local EFL teachers to supplement and eventually replace expatriate teachers.  It is concluded that ownership and commitment on EFL programmes are directly related to issues of autonomy and control, and that striking a balance between autonomy and control is a very difficult aspect of programme management.  Keywords:      EFL, management, mentor programme design,   autonomy, control, ownership,